Enhancement of the Quantum Dot Luminescence in All-Dielectric Metamaterial - Khardikov, V.V.; Prosvirnin, S.L. (Радиофизика и радиоастрономия, 2013)
We propose a simple design of an all-dielectric silicon-based planar metamaterial that manifests an extremely sharp resonant reflection and transmission at the wavelength of about 1550 nm due to both low dissipative losses and the trapped mode operating method particularities. The resonance Q-factor dozens of times exceeds that of resonances in the common infrared plasmonic structures. The designed metamaterial is considered for aggregation with a pumped gain medium to achieve the enhancement of luminescence and produce an all-dielectric analog of a “lasing spaser”. We report that an essential enhancement (above 500 times) of luminescence of a layer containing pumped quantum dots can be achieved by using the designed metamaterial. This value scores of times exceeds the known luminescence enhancement by the plasmonic planar metamaterials.